Nancy Drew - Weintraub, Jerry; Paulsen, Tiffany; Fleming, Andrew, 1963-; Roberts, Emma, 1991-; Flitter, Josh.; Gellis, Craig; Cooper, Rich.; Thieriot, Max.; Cook, Rachael Leigh, 1979-; Bruckner, Amy.; Donovan, Tate.; Bostwick, Barry; et al. (Burbank, Calif. : Warner Home Video, 2008)
Girl detective Nancy Drew is about to experience a serious case of culture shock as she heads to Hollywood with her father, Carson Drew. Having promised him that she has given up sleuthing, Nancy tries her best to resist the lure of the age-old mystery of famous actress Dehlia Draycott's death. .
Standard and widescreen versions.
Based on the characters created by Carolyn Keene.
DVD release of the 2007 motion picture.
Special features: 'Nancy Drew: kids at work' featurette; gag reel; 'Pretty much amazing' music video by Joanna; mini-featurette gallery: cool scenes with the cast and crew.
Director of photography, Alexander Gruszynski ; editor, Jeff Freeman ; music, Ralph Sall ; costume designer, Jeffrey Kurland ; production designer, Tony Fanning.
Emma Roberts, Josh Flitter, Craig Gellis, Rich Cooper, Max Thieriot, Rachael Leigh Cook, Amy Bruckner, Tate Donovan, Barry Bostwick, Kay Panabaker, Cliff Bemis, David Doty, Laura Elena Harring.
Keywords: Drew, Nancy (Fictitious character) -- Juvenile drama; Women detectives -- California -- Los Angeles -- Juvenile drama; Criminal investigation -- California -- Los Angeles -- Juvenile drama; High school students -- California -- Los Angeles -- Juvenile drama; High school student activities -- California -- Los Angeles -- Juvenile drama; Hollywood (Los Angeles, Calif.) -- Juvenile drama; Feature films; Comedy films; Detective and mystery films; Films for the hearing impaired